1987
DOI: 10.1099/00207713-37-2-136
|View full text |Cite
|
Sign up to set email alerts
|

Xylella fastidiosa gen. nov., sp. nov: Gram-Negative, Xylem-Limited, Fastidious Plant Bacteria Related to Xanthomonas spp.

Abstract: Twenty-five phenotypically and genotypically similar strains of a fastidious, xylem-limited bacterium were isolated from 10 plant disease sources including Pierce's disease of grapevines, phony disease of peach, periwinkle wilt, and leaf scorches of almond, plum, elm, sycamore, oak, and mulberry. The cells were single (occasionally filamentous), nonmotile, aflagellate straight rods (0.25 to 0.35 by 0.9 to 3.5 pm). They were gram negative, catalase positive, and oxidase negative, utilized hippurate, and produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
308
0
84

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(427 citation statements)
references
References 37 publications
6
308
0
84
Order By: Relevance
“…(Wells et al, 1987), and the grapevine strains GR.8935 T and GR.9713 were isolated in the USA, and the pear strain PE.PLS was isolated in Taiwan. The strains were cultivated on solid buffered cysteine\yeast extract (BCYE) medium (Wells et al, 1981a) for a period of approximately 10 d at 28 mC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wells et al, 1987), and the grapevine strains GR.8935 T and GR.9713 were isolated in the USA, and the pear strain PE.PLS was isolated in Taiwan. The strains were cultivated on solid buffered cysteine\yeast extract (BCYE) medium (Wells et al, 1981a) for a period of approximately 10 d at 28 mC.…”
Section: Methodsmentioning
confidence: 99%
“…Strains used for sequencing were chosen on the basis of different groups observed by PCR-RFLP of the 16S rDNA and the 16S-23S intergenic spacer (Rosato et al, 1998 ;Mehta et al, 1999a, c). In all analyses, the type strain of Xylella fastidiosa, GR.8935 T (l ATCC 35879 T ), which corresponds to strain PCE-RR (Wells et al, 1987), was used.…”
Section: Methodsmentioning
confidence: 99%
“…Only in the mid-1970s, after it was shown that 'yellows' diseases of plants were of bacterial origin (phytoplasmas and spiroplasmas; Doi et al 1967), were diseases caused by X. fastidiosa determined to also have bacterial etiology (Hopkins and Mollenhauer 1973). That breakthrough led to its axenic culture in 1978 (Davis et al 1978); and the bacterium was named X. fastidiosa one decade later (Wells et al 1987). Despite its importance, research on this pathogen remained limited until a new disease in citrus emerged in Brazil in 1987 and another reemerged in California in the late 1990s (Hopkins and Purcell 2002).…”
Section: Historymentioning
confidence: 99%
“…Xylella fastidiosa is a gamma-proteobacterium in the order Xanthomonadales, family Xanthomonadaceae (Wells et al 1987). This is the single species in the genus Xylella, which is monophyletic, and has Xanthomonas ssp.…”
Section: Taxonomymentioning
confidence: 99%
“…Xylella fastidiosa (Xf) is a xylem-limited gram-negative plant pathogenic bacterium, which causes diseases in many plants, including Pierce's disease (PD) in grapevine [1]. In diseased plants, X. fastidiosa cells are embedded in the plant vessel matrix in clumps (biofilm) and result in the blockage of the water flow within the xylem vessels.…”
Section: Introductionmentioning
confidence: 99%